PENULISAN SASTRA ANAK - Enny Zubaidah (LPMPP Universitas Negeri Yogyakarta, 2003)
Any effort to develop human beings with a sensitive, selfdependent, and responsible character could start from the time theyare still atan early age and even from the time they are still in theirmother's womb. After a childis born, such an effort can be doneboth in the home environment and outside it, including the timewhen the child gains education at school and outside it because therethe child getsmodels. At school it can be done by making the childlistento a story read' or retold by the teacher. Therefore, the teacherhad better have a motivation andan ability to write a story forchildren. Because the story, as a part of children's literature, ispresented to children, its elements should be chosen from objectsfound around children and events usually experiencedby children.The language used shouldbe in accordance with the child's age andpsychological development. The writing technique should involvethe story-building elements, or the story's mental structures, whichinclude its(I) plot, (2) characterization, (3) story-telling style, (4)setting, and(5) theme. Besides that, attention should also be paid tophysical elements in the sense that (I) the text in the storybookshouldbe accompanied with attractive pictures; (2) the form and sizeof the letters should make them easily perceived by children who arestill learning to read, and (3) the paper should be sufficiently thickandofgood quality.